(untitled) (European Journal of Marketing and Economics, 2019)
In modern states, economic system of state it function through financing institutions. So, financing system plays an important role in business and economic activities. Bankrupty and liquidation process in finance sector in Kosovo has intended avoiding the failure of the economic enterprise and its one of the important cases in finance direction. Therefore, studies of this form shows a big interes from scientific researcher in our state and wider. This paper is focused in bankrupty and liquidation process of finance institutions, studing the most important elements of bankrupty and liquidation process in out place and region. Research model gives a visual describe of research and this topic elaborates very well. Financing institution are registered and licensed from CBK and it consisting of: Banks, Pension Funds, Ensurance Companies, microfinancial institutions and other nonbank financial institutions. Central Bank of Kosovo (CBK) has executive responsibilities for licensing/ registering and monitoring financial institutions such as: banks, ensurance company, pension funds, microfinancial institutions, nonbank financing institutions and other legal subjects that exercising financial activity with Kosovo legislation.As th bankrupty process starts ealry, by taking signals from financial indicators, research preliminarly do actual evaluation of finance statements of financial institutions. The purpose of this paper is to give general frame of bankrupty and liquidation of financial institutions in Kosovo. Financial performance measurement which is thought to be a model of performance is limited with CAMEL model for banks and Dupont model for other financial institutions. Excepted of those, research is a subject of only financial institutions in Kosovo, so it could not be generalized.